Battery and electric device

CN123017958APending Publication Date: 2026-10-30CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611191271.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-26
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]鉴于背景技术中存在的技术问题,本申请提供一种正极活性材料,旨在解决含有其的电池循环稳定性较差的问题

Benefits of technology

[0038]本申请的附加方面和优点将在下面的描述中部分给出,部分将从下面的描述中变得明显,或通过本申请的实践了解到。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017958A_ABST
    Figure CN123017958A_ABST
Patent Text Reader

Abstract

The application provides a positive electrode active material, a preparation method thereof, a positive electrode sheet, a battery and an electric device. The positive electrode active material comprises: Na x Mn y L a M b N c O 2‑z‑δ F z , wherein L comprises at least one of Ni, Li, Zn, Cu, Mg, Fe, B, Al, La, Cr, In and Ga, M comprises at least one of Ti, Sn, Sb, Bi and Zr, N comprises at least one of Nb, Ta, Mo and W, 0.5<=x<=1.2, y>=0.2, 0.1<=a<=0.6, 0<=b<=0.3, 0
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Case Separation Statement This application is a divisional application of the invention patent application with application number 202310759586.9, application date June 26, 2023, entitled "Positive electrode active material and preparation method, positive electrode sheet, battery and electrical device". Technical Field

[0002] This application relates to the field of battery technology, specifically to positive electrode active materials and preparation methods, positive electrode sheets, batteries, and electrical devices. Background Technology

[0003] Batteries are not only used in energy storage power systems such as hydropower, thermal power, wind power and solar power plants, but also widely used in electric vehicles such as electric bicycles, electric motorcycles and electric cars, as well as in military equipment and aerospace and other fields.

[0004] Sodium-ion batteries are a type of battery, and layered transition metal oxides are commonly used positive electrode active materials in sodium-ion batteries. However, existing positive electrode active materials containing layered transition metal oxides have poor cycle stability. Summary of the Invention

[0005] In view of the technical problems existing in the background art, this application provides a positive electrode active material, which aims to solve the problem of poor cycle stability of batteries containing it.

[0006] The first aspect of this application discloses a positive electrode active material, said positive electrode active material comprising: Na x Mn y L a M b N c O 2-z-δ F z Wherein, L includes at least one of Ni, Li, Zn, Cu, Mg, Fe, B, Al, La, Cr, In, and Ga; M includes at least one of Ti, Sn, Sb, Bi, and Zr; N includes at least one of Nb, Ta, Mo, and W; 0.5 ≤ x ≤ 1.2, y ≥ 0.2, 0.1 ≤ a ≤ 0.6, 0 ≤ b ≤ 0.3, 0 <c≤0.05,y+a+b+c=1,0≤z≤0.1,-0.1≤δ≤0.1,40≤a / c≤400。

[0007] The nitrogen element (including at least one of Nb, Ta, Mo, and W) in the cathode active material proposed in this application has a strong interaction with oxygen. Under high pressure, it can stabilize the oxygen in the cathode active material lattice, reducing the risk of oxygen loss and the probability of structural collapse and metal dissolution. This reduces the risk of capacity loss due to cracks forming on the cathode active material during battery cycling, thus improving the cycle stability of batteries containing the aforementioned cathode active material. In addition, the cathode active material also includes nitrogen (L) elements that can form low-valence ions. While nitrogen interacts with oxygen, the low-valence L ions can reduce the risk of excessive local charge and structural deformation caused by the high valence of nitrogen ions. This improves the stability of the cathode active material while increasing the diffusion rate of sodium ions and thus increasing the specific capacity. In this application, 40 ≤ a / c ≤ 400 effectively reduces the risk of crack formation in the cathode active material during battery cycling, while simultaneously improving the structural stability of the cathode active material and the cycle stability of batteries containing the aforementioned cathode active material.

[0008] In some implementations, 50 ≤ a / c ≤ 200. This reduces the risk of excessive local charge in the positive electrode active material due to the high valence state of N ions, which could lead to structural deformation of the positive electrode active material. It also improves the stability of the positive electrode active material, increases the diffusion rate of sodium ions, enhances the specific capacity of the positive electrode active material, and improves the cycle stability of batteries containing the aforementioned positive electrode active material.

[0009] In some embodiments, N includes at least one of Nb and Ta. This reduces the risk of oxygen loss from the positive electrode active material, improves the specific capacity of the positive electrode active material, and enhances the cycle stability of batteries containing the aforementioned positive electrode active material.

[0010] In some embodiments, L includes at least one of Ni, Zn, Cu, Mg, Fe, B, and Al.

[0011] In some implementations, M includes at least one of Ti, Bi, and Zr.

[0012] In some implementations, 0.7 ≤ x ≤ 1.

[0013] In some implementations, 0.3 ≤ y ≤ 0.5.

[0014] In some implementations, 0.4 ≤ a ≤ 0.6.

[0015] In some implementations, 0.01 ≤ b ≤ 0.1.

[0016] In some implementations, 0.005 ≤ c ≤ 0.015.

[0017] In some implementations, 0 ≤ z ≤ 0.005.

[0018] This can improve the specific capacity and cycle stability of the positive electrode active material.

[0019] In some implementations, 3 ≤ y / (b+c) ≤ 40. This allows for the formation of disordered sodium vacancy arrangements in the positive electrode active material during battery cycling, suppressing irreversible phase transitions, increasing the specific capacity of the positive electrode active material, and improving its stability during battery cycling.

[0020] In some implementations, 6 ≤ y / (b+c) ≤ 30.

[0021] In some embodiments, the phase state of the positive electrode active material includes the O3 phase, and the space group of the positive electrode active material with the O3 phase includes... The interlayer spacing of the O3 phase positive electrode active material is 0.53 nm-0.55 nm. Therefore, the O3 phase positive electrode active material has a high Na content, which can improve the battery capacity.

[0022] In some embodiments, the positive electrode active material comprises a P2 phase, the space group of the P2 phase positive electrode active material comprises P63 / mmc, and the interlayer spacing of the P2 phase positive electrode active material is 0.54 nm-0.57 nm. Therefore, the large interlayer spacing of the formed P2 phase positive electrode active material can improve the rate performance and cycle performance of the battery.

[0023] In some embodiments, the pH value of the immersion solution for the positive electrode active material is 7-13 at 25°C.

[0024] In some embodiments, the pH value of the immersion solution for the positive electrode active material is 11-12.5 at 25°C.

[0025] In some embodiments, the particle size D of the positive electrode active material v 50 is 3μm-30μm.

[0026] In some embodiments, the particle size D of the positive electrode active material v 50 is 5μm-15μm.

[0027] In some embodiments, the specific surface area of ​​the positive electrode active material is 0.1 m². 2 / g-5m 2 / g.

[0028] In some embodiments, the specific surface area of ​​the positive electrode active material is 0.3 m². 2 / g-3m2 / g.

[0029] In some embodiments, the tap density of the positive electrode active material is 1 g / cm 3 -3 g / cm 3 .

[0030] In some embodiments, the tap density of the positive electrode active material is 1.5 g / cm 3 -2.5 g / cm 3 .

[0031] In some embodiments, the compaction density of the positive electrode active material under a pressure of 300 MPa is 3.0 g / cm 3 -4.0 g / cm 3 .

[0032] Accordingly, when at least one of D v 50, specific surface area, tap density and compaction density under 300 MPa pressure of the positive electrode active material is within the above ranges, the conduction distance of Na ions in the positive electrode active material is short, the surface side reactions are few, the positive electrode active material is promoted to exert its gram capacity, and the capacity retention rate of a battery containing the same is improved.

[0033] In a second aspect of the present application, a method for preparing a positive electrode active material is provided, comprising: mixing a Na source, a Mn source, an L source, an M source and an N source to obtain a precursor, wherein the molar content of Na in the Na source is x, the molar content of Mn in the Mn source is y, the molar content of L in the L source is a, the molar content of M in the M source is b, the molar content of N in the N source is c, wherein L comprises at least one of Ni, Li, Zn, Cu, Mg, Fe, B, Al, La, Cr, In and Ga, M comprises at least one of Ti, Sn, Sb, Bi and Zr, N comprises at least one of Nb, Ta, Mo and W, 0.5≤x≤1.2, y≥0.2, 0.1≤a≤0.6, 0≤b≤0.3, 0<c≤0.05, y+a+b+c=1, 40≤a / c≤400; and calcining the precursor to obtain the positive electrode active material, wherein the positive electrode active material comprises Na x Mn y L a M b N c O 2-z-δ F z , 0≤z≤0.1, -0.1≤δ≤0.1. Accordingly, the positive electrode active material prepared by the present application has high specific capacity and excellent cycle stability.

[0034] A third aspect of the present application provides a method for preparing a positive electrode active material, comprising: mixing an Mn source, an L source, an M source, and an N source with water to obtain a mixed solution, wherein the molar content of Mn in the Mn source is y, the molar content of L in the L source is a, the molar content of M in the M source is b, and the molar content of N in the N source is c, L includes at least one of Ni, Li, Zn, Cu, Mg, Fe, B, Al, La, Cr, In and Ga, M includes at least one of Ti, Sn, Sb, Bi and Zr, N includes at least one of Nb, Ta, Mo and W, y≥0.2, 0.1≤a≤0.6, 0≤b≤0.3, 0<c≤0.05, y+a+b+c=1, 40≤a / c≤400; reacting the mixed solution with a precipitant to obtain a precursor; mixing the precursor with a Na source and then performing calcination, wherein the molar content of Na in the Na source is x, 0.5≤x≤1.2, to obtain the positive electrode active material, and the positive electrode active material comprises Na x Mn y L a M b N c O 2-z-δ F z , 0≤z≤0.1, -0.1≤δ≤0.1. Accordingly, the positive electrode active material prepared by the present application has high specific capacity and excellent cycle stability.

[0035] A fourth aspect of the present application provides a positive electrode plate, comprising the positive electrode active material according to the first aspect of the present application or the positive electrode active material prepared by the method according to the second or third aspect of the present application.

[0036] A fifth aspect of the present application provides a battery, comprising the positive electrode plate according to the fourth aspect of the present application. Accordingly, the battery has excellent cycle performance.

[0037] A sixth aspect of the present application provides an electrical device, comprising the battery according to the fifth aspect of the present application.

[0038] Additional aspects and advantages of the present application will be partially set forth in the following description, and will partially become apparent from the following description, or be learned through practice of the present application. Brief Description of the Drawings

[0039] Upon reading the following detailed description of the preferred embodiments, various other advantages and benefits will become clear to those of ordinary skill in the art. The drawings are only for the purpose of illustrating preferred embodiments and are not to be construed as limiting the present application. Moreover, the same reference numerals denote the same components throughout the drawings. In the drawings: Figure 1 is a schematic structural view of a battery according to an embodiment of the present application; Figure 2 This is a schematic diagram of the structure of a battery module according to one embodiment of this application; Figure 3 This is a schematic diagram of the structure of a battery pack according to one embodiment of this application; Figure 4 yes Figure 3 Exploded view; Figure 5 This is a schematic diagram of one embodiment of an electrical device that uses a battery as a power source; Figure 6 This is a comparison chart of capacity retention rates between Example 18 and Comparative Example 4; Figure 7 This is a scanning electron microscope image of Example 18; Figure 8 This is a scanning electron microscope image of Comparative Example 4.

[0040] Explanation of reference numerals in the attached figures: 1: Battery; 2: Battery module; 3: Battery pack; 4: Upper casing; 5: Lower casing. Detailed Implementation

[0041] The embodiments of the technical solution of this application are described in detail below. The following embodiments are only used to illustrate the technical solution of this application more clearly, and are therefore only examples, and should not be used to limit the scope of protection of this application.

[0042] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0043] For the sake of brevity, this article only discloses some specific numerical ranges. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, just as any upper limit can be combined with any other upper limit to form an unspecified range. Furthermore, each individually disclosed point or single value can itself serve as a lower or upper limit and be combined with any other point or single value, or with other lower or upper limits, to form an unspecified range.

[0044] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.

[0045] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.

[0046] With the technological advancements and increasing demands for electric vehicles and rechargeable mobile devices, batteries, as a representative of the new energy field, have seen rapid development in related research. Sodium-ion batteries offer a significant price advantage over traditional lithium-ion batteries and have broad application prospects in large-scale energy storage systems.

[0047] Layered transition metal oxides (LTMOs) have become a popular cathode active material for sodium-ion batteries due to their high conductivity, high energy density, large capacity, and long cycle life. However, during the sodium insertion / extraction process, LTMOs are prone to oxygen loss, leading to structural collapse and metal dissolution of the cathode active material. This reduces the stability of the cathode active material structure and consequently decreases the specific capacity and cycle stability of batteries containing these materials.

[0048] The positive electrode active material proposed in this application incorporates nitrogen (N) elements, which can form high-valence ions. These elements have a strong interaction with oxygen, thereby stabilizing the oxygen in the crystal lattice of the positive electrode active material, reducing the risk of oxygen loss, and minimizing capacity loss during cycling in batteries containing this positive electrode active material. Simultaneously, to prevent excessive localized charge in the positive electrode active material, elements that can form low-valence ions are also included to balance the charge distribution, improve the structural stability of the positive electrode active material, and thus enhance the cycle stability of batteries containing this positive electrode active material. This application specifies the relative amounts of nitrogen (L) and nitrogen (N) elements to improve the specific capacity and structural stability of the positive electrode active material.

[0049] The positive electrode active material disclosed in this application is suitable for batteries, and the batteries disclosed in this application can be used in electrical devices that use batteries as a power source or in various energy storage systems that use batteries as energy storage elements. Electrical devices may include, but are not limited to, mobile phones, tablets, laptops, electric toys, power tools, electric vehicles, electric cars, ships, spacecraft, etc. Electric toys may include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc. Spacecraft may include airplanes, rockets, space shuttles, and spacecraft, etc.

[0050] The first aspect of this application discloses a positive electrode active material, said positive electrode active material comprising: Nax Mn y L a M b N c O 2-z-δ F z Wherein, L includes at least one of Ni, Li, Zn, Cu, Mg, Fe, B, Al, La, Cr, In, and Ga; M includes at least one of Ti, Sn, Sb, Bi, and Zr; N includes at least one of Nb, Ta, Mo, and W; 0.5 ≤ x ≤ 1.2, y ≥ 0.2, 0.1 ≤ a ≤ 0.6, 0 ≤ b ≤ 0.3, 0 <c≤0.05,0≤z≤0.1,-0.1≤δ≤0.1,40≤a / c≤400。

[0051] The nitrogen element (including at least one of Nb, Ta, Mo, and W) in the cathode active material proposed in this application has a strong interaction with oxygen. Under high pressure, it can stabilize the oxygen in the cathode active material lattice, reducing the risk of oxygen loss and the probability of structural collapse and metal dissolution. This reduces the risk of capacity loss due to cracks forming on the cathode active material during battery cycling, thus improving the cycle stability of batteries containing the aforementioned cathode active material. In addition, the cathode active material also includes nitrogen (L) elements that can form low-valence ions. While nitrogen interacts with oxygen, the low-valence L ions can reduce the risk of excessive local charge and structural deformation caused by the high valence of nitrogen ions. This improves the stability of the cathode active material while increasing the diffusion rate of sodium ions and thus increasing the specific capacity. In this application, 40 ≤ a / c ≤ 400 effectively reduces the risk of crack formation in the cathode active material during battery cycling, while simultaneously improving the structural stability of the cathode active material and the cycle stability of batteries containing the aforementioned cathode active material.

[0052] In some embodiments, the above-mentioned positive electrode active material Na x Mn y L a M b N c O 2-z-δ F z The value is 0.5 ≤ x ≤ 1.2, for example, it can be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, or 1.2, or any range of the above values. In some specific embodiments, 0.7 ≤ x ≤ 1. Therefore, the positive electrode active material includes this amount of sodium, resulting in a higher battery capacity.

[0053] It should be noted that in the positive electrode, battery, or electrical device, sodium ions are consumed during the formation and cycling processes, resulting in a measured sodium content (x) in the positive electrode active material that is less than 1. Conversely, if sodium replenishment agents are used in both the positive and negative electrode sheets, the measured sodium content (x) in the positive electrode active material will be greater than 1 after the battery undergoes formation and cycling.

[0054] In some embodiments, the above-mentioned positive electrode active material Na x Mn y L a M b N c O 2-z-δ F z L in the cathode material includes at least one of Ni, Zn, Cu, Mg, Fe, B, and Al. This reduces the risk of excessive local charge in the cathode active material due to the high valence state of N ions, which could lead to structural deformation. It also improves the stability of the cathode active material, increases the diffusion rate of sodium ions, enhances the specific capacity of the cathode active material, and improves the cycle stability of batteries containing the aforementioned cathode active material.

[0055] In some embodiments, the above-mentioned positive electrode active material Na x Mn y L a M b N c O 2-z-δ F z The value is 0.1 ≤ a ≤ 0.6, for example, it can be 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, or 0.6, or a range of any of the above values. In some specific embodiments, 0.4 ≤ a ≤ 0.6. Therefore, the positive electrode active material includes this amount of sodium, resulting in a higher battery capacity.

[0056] In some embodiments, the above-mentioned positive electrode active material Na x Mn y L a M b N c O 2-z-δ F z M in the cathode material includes at least one of Ti, Bi, and Zr. This allows for the formation of ions with higher valence states, resulting in a disordered sodium vacancy arrangement on the cathode active material during battery cycling, suppressing irreversible phase transitions, and improving the cycle stability of the cathode active material.

[0057] In some embodiments, the above-mentioned positive electrode active material Na x Mn y La M b N c O 2-z-δ F z where 0≤b≤0.3, for example, may be 0.02, 0.04, 0.06, 0.08, 0.1, 0.12, 0.14, 0.16, 0.18, 0.2, 0.22, 0.24, 0.26, 0.28 or 0.3, etc., or may be a range composed of any of the above values. As a result, the M element can form a strong chemical bond with oxygen, inhibit the extraction of sodium element in the positive electrode active material, and further improve the capacity of a battery containing the above positive electrode active material.

[0058] In some embodiments, the above positive electrode active material Na x Mn y L a M b N c O 2-z-δ F z wherein N includes at least one of Nb and Ta. As a result, Nb and Ta have strong interaction with oxygen, which can stabilize oxygen in the crystal lattice of the positive electrode active material under high voltage, reduce the risk of oxygen loss in the positive electrode active material, reduce the probability of structural collapse of the positive electrode active material and metal dissolution, and reduce the risk of battery capacity loss caused by cracks formed on the positive electrode active material during battery cycling.

[0059] In some embodiments, the above positive electrode active material Na x Mn y L a M b N c O 2-z-δ F z where 0<c≤0.05, for example, may be 0.005, 0.01, 0.015, 0.02, 0.025, 0.03, 0.035, 0.04, 0.045 or 0.05, etc., or may be a range composed of any of the above values. In some specific embodiments, 0.005≤c≤0.015.

[0060] In some embodiments, the above positive electrode active material Na x Mn y L a M b N c O 2-z-δ F zThe value 40 ≤ a / c ≤ 400, for example, can be 40, 60, 80, 100, 120, 140, 160, 180, 200, 220, 240, 260, 280, 300, 320, 340, 360, 380, or 400, or any range of the above values. In some specific embodiments, 50 ≤ a / c ≤ 200. Therefore, while reducing the risk of oxygen loss from the positive electrode active material and increasing battery capacity, it also improves the stability and cycle stability of the positive electrode active material.

[0061] In some embodiments, the above-mentioned positive electrode active material Na x Mn y L a M b N c O 2-z-δ F z In this context, 0 ≤ z ≤ 0.1, and -0.1 ≤ δ ≤ 0.1. For example, z can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, or 0.1, or a range of any of the above values. Similarly, δ can be -0.1, -0.09, -0.08, -0.07, -0.06, -0.05, -0.04, -0.03, -0.02, -0.01, 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, or 0.1, or a range of any of the above values. In some specific implementations, 0 ≤ z ≤ 0.005. Specifically, the oxygen sites in the positive electrode active material of this application are doped with this amount of F, which can effectively stabilize the oxygen in the positive electrode active material, thereby reducing the structural damage caused by the release of oxygen from the lattice in the positive electrode active material, improving the stability of the material, and thus improving the capacity retention rate of the battery.

[0062] It should be noted that in positive electrode sheets, batteries, or electrical devices, oxygen elements in the positive electrode active material are lost due to processes such as battery cycling. Therefore, the measured oxygen content 2-z-δ in the positive electrode active material may be less than 2.

[0063] In some embodiments, the above-mentioned positive electrode active material Na x Mn y L a M b N c O 2-z-δ F zIn the given condition, y ≥ 0.2. In some specific embodiments, 0.3 ≤ y ≤ 0.5. For example, y can be 0.3, 0.32, 0.34, 0.36, 0.38, 0.4, 0.42, 0.44, 0.46, 0.48, or 0.5, or a range of any of the above values. Therefore, manganese ions have a high valence state, which can effectively stabilize the layered structure, suppress the leakage of metal ions from the positive electrode active material, and improve the cycle stability of the positive electrode active material.

[0064] In some embodiments, the above-mentioned positive electrode active material Na x Mn y L a M b N c O 2-z-δ F z The value 3 ≤ y / (b+c) ≤ 40, for example, can be 3, 5, 7, 9, 11, 13, 15, 17, 19, 21, 23, 25, 27, 29, 31, 33, 35, 37, 39, or 40, or any range of the above values. In some specific embodiments, 6 ≤ y / (b+c) ≤ 30. Thus, M and N elements can form ions with higher valence states, which can lead to disordered sodium vacancy arrangements on the positive electrode active material during battery cycling, suppressing irreversible phase transitions and improving the cycle stability of the positive electrode active material. Mn element can stabilize the structure of the layered positive electrode active material, allowing M and N elements to be doped into the lattice of the positive electrode active material, thereby increasing the specific capacity of the positive electrode active material. By limiting the content of M, N, and Mn elements to satisfy 3 ≤ y / (b+c) ≤ 40, the specific capacity of the positive electrode active material can be improved while simultaneously enhancing its cycle stability.

[0065] In some embodiments, the phase state of the positive electrode active material may include the O3 phase, and the space group of the positive electrode active material with the O3 phase may include... The interlayer spacing of the O3 phase positive electrode active material can be between 0.53 nm and 0.55 nm. For example, the interlayer spacing of the O3 phase positive electrode active material can be 0.53 nm, 0.532 nm, 0.534 nm, 0.536 nm, 0.538 nm, 0.54 nm, 0.542 nm, 0.544 nm, 0.546 nm, 0.548 nm, or 0.55 nm, or a range of any of the above values. Therefore, the O3 phase positive electrode active material has a high sodium content, which can improve the battery capacity.

[0066] In some embodiments, the phase state of the positive electrode active material may further include a P2 phase. The space group of the P2 phase positive electrode active material may include P63 / mmc, and the interlayer spacing of the P2 phase positive electrode active material may be 0.54 nm-0.57 nm. For example, the interlayer spacing of the P2 phase positive electrode active material may be 0.54 nm, 0.544 nm, 0.548 nm, 0.552 nm, 0.556 nm, 0.56 nm, 0.564 nm, 0.568 nm, or 0.57 nm, or may be any range of the above values. Therefore, the large interlayer spacing of the formed P2 phase positive electrode active material can improve the rate performance and cycle performance of the battery.

[0067] In some embodiments, at 25°C, the pH value of the soaking solution for the positive electrode active material can be 7-13. For example, the pH value of the soaking solution for the positive electrode active material can be 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, 12, 12.5, or 13, or any range of the above values. Therefore, controlling the pH value of the soaking solution for the positive electrode active material within the above range can reduce the probability of gel formation during the slurry preparation process, facilitating subsequent slurry preparation and coating of the positive electrode active material. In some specific embodiments, the pH value of the soaking solution for the positive electrode active material can be 11-12.5.

[0068] Specifically, the pH value of the immersion solution for the positive electrode active material can be measured using the following method: Take 2g of positive electrode active material and place it in a beaker. Add 18mL of deionized water and stir vigorously for 1min. After standing for 30min, use a pH meter to test the pH of the supernatant.

[0069] In some embodiments, the particle size D of the positive electrode active material v 50 can be 3μm-30μm, for example, D v 50 can be 3μm, 5μm, 7μm, 9μm, 11μm, 13μm, 15μm, 17μm, 19μm, 21μm, 23μm, 25μm, 27μm, 29μm, or 30μm, or a range of any of the above values. In some specific embodiments, D v The size of the material can range from 5μm to 15μm. As a result, the sodium ions in the positive electrode active material have a short conduction distance and fewer surface side reactions, which promotes the specific capacity of the positive electrode active material and improves the capacity retention rate of batteries containing it.

[0070] In this application, D v50 refers to the particle size corresponding to a cumulative volumetric distribution percentage of 50%. For example, according to standard GB / T 19077-2016 / ISO 13320:2009, the particle size is measured using a laser particle size analyzer (Malvern Master Size 2000). The specific testing procedure is as follows: Take an appropriate amount of the sample to be tested (the sample concentration should be 8%-12% light-blocking), add 20 ml of deionized water, and sonicate for 5 minutes (53 kHz / 120 W) to ensure complete dispersion of the sample. Then, measure the sample according to the standard GB / T19077-2016 / ISO13320:2009.

[0071] In some embodiments, the specific surface area of ​​the positive electrode active material can be 0.1 m². 2 / g-5m 2 / g, for example, the specific surface area of ​​the positive electrode active material can be 0.1m². 2 / g, 0.5m 2 / g, 1m 2 / g, 1.5m 2 / g、2m 2 / g, 2.5m 2 / g、3m 2 / g, 3.5m 2 / g、4m 2 / g, 4.5m 2 / g or 5m 2 / g, etc., or can be any range of the above values. In some specific embodiments, the specific surface area of ​​the positive electrode active material can be 0.3m². 2 / g-3m 2 / g. As a result, the sodium ions in the positive electrode active material have a short conduction distance and fewer surface side reactions, which promotes the positive electrode active material to exert its specific capacity and improves the capacity retention rate of batteries containing it.

[0072] In this application, the specific surface area of ​​the positive electrode active material can be obtained by the following method: using a US-made Gemini VII2390 multi-station fully automated specific surface area and porosity analyzer, take about 7g of sample and put it into a 9cc long tube with a bulb, degas at 200℃ for 2h, and then put it into the main unit to test and obtain the BET (specific surface area) data of the positive electrode active material.

[0073] In some embodiments, the tap density of the positive electrode active material can be 1 g / cm³. 3 -3g / cm 3 For example, the tap density of the positive electrode active material can be 1 g / cm³. 3 1.2g / cm 3 1.4g / cm 31.6g / cm 3 1.8g / cm 3 2g / cm 3 2.2g / cm 3 2.4g / cm 3 2.6g / cm 3 2.8g / cm 3 Or 3g / cm 3 etc., or can be any range of the above values. In some specific embodiments, the tap density of the positive electrode active material can be 1.5 g / cm³. 3 -2.5g / cm 3 Therefore, the short conduction distance of sodium ions and fewer surface side reactions in the positive electrode active material promote the specific capacity of the positive electrode active material and improve the capacity retention rate of batteries containing it.

[0074] In this application, tap density refers to the mass per unit volume of powder in a container after tapping under specified conditions. The method for determining the tap density of positive electrode active materials is as follows: The weighed positive electrode active material is loaded into the graduated cylinder of the tapping device, and the graduated cylinder is fixed on the support. Rotating the cam causes the guide rod to slide the support up and down, striking the anvil. The device vibrates at 250±15 times per minute for 12 minutes. The volume of the positive electrode active material in the graduated cylinder is measured; the ratio of the mass of the positive electrode active material to its volume is the tap density of the positive electrode active material.

[0075] The formula for calculating tap density is: ρbt = m0 / V Where ρbt is the tap density, in g / cm³. 3 m0 — Mass of the positive electrode active material, in grams V – Volume of the positive electrode active material after tapping (volume of the measuring cup), cm 3 .

[0076] In some embodiments, the compaction density of the positive electrode active material under a pressure of 300 MPa can be 3.0 g / cm³. 3 -4.0g / cm 3 For example, the compaction density of the positive electrode active material under a pressure of 300 MPa can be 3.0 g / cm³. 3 3.2g / cm 3 3.4g / cm 3 3.6g / cm 3 3.8g / cm 3 or 4g / cm 3The values ​​can be any range of the above values. Therefore, the short conduction distance of sodium ions within the positive electrode active material and the few surface side reactions promote the effective utilization of the specific capacity of the positive electrode active material and improve the capacity retention rate of batteries containing it.

[0077] In this application, compaction density refers to the compaction density of the electrode sheet after the material is made into an electrode sheet. Compaction density = areal density / (thickness of the electrode sheet after compaction - thickness of the current collector). Specifically, the method for determining the compaction density of the positive electrode active material under a pressure of 300 MPa refers to GB / T5162-2006.

[0078] The second aspect of this application discloses a method for preparing a positive electrode active material, comprising: S100: A precursor is obtained by mixing Na source, Mn source, L source, M source and N source. Specifically, a precursor is obtained by mixing a Na source, a Mn source, an L source, an M source, and an N source. The molar content of Na in the Na source is x, the molar content of Mn in the Mn source is y, the molar content of L in the L source is a, the molar content of M in the M source is b, and the molar content of N in the N source is c. Wherein, L includes at least one of Ni, Li, Zn, Cu, Mg, Fe, B, Al, La, Cr, In, and Ga; M includes at least one of Ti, Sn, Sb, Bi, and Zr; and N includes at least one of Nb, Ta, Mo, and W. The molar content is 0.5 ≤ x ≤ 1.2, 0.2 ≤ y, 0.1 ≤ a ≤ 0.6, 0 ≤ b ≤ 0.3, and 0 ≤ ... <c≤0.05,y+a+b+c=1,40≤a / c≤400。

[0079] It should be noted that the Na source, Mn source, L source, M source, and N source in this application are conventional materials in the art, and those skilled in the art can select them according to actual needs. For example, the Na source may include at least one of Na2CO3, NaHCO3, NaOH, and Na2O2; the Mn source may include at least one of Mn2O3, Mn3O4, MnO, and MnO2; the L source may include at least one of L oxides, L-containing salts, and other compounds; the M source may include at least one of M oxides, M-containing salts, and other compounds; and the N source may include at least one of N oxides, N-containing salts, and other compounds.

[0080] It should be noted that if F element needs to be doped in the positive electrode active material, at least one of the Na source, Mn source, L source, M source and N source shall be at least one of its corresponding fluorine-containing salt and other compounds, such as sodium fluoride, manganese fluoride, L fluoride (fluoride salt of L), M fluoride (fluoride salt of M) and N fluoride (fluoride salt of N).

[0081] It should be noted that, since Na is lost during calcination, the molar content of Na can be appropriately increased when feeding to compensate for the loss of Na during calcination.

[0082] S200: The precursor is calcined to obtain the positive electrode active material. In some embodiments of this application, the precursor obtained in S100 is calcined in a muffle furnace, cooled to room temperature, and then mechanically pulverized to obtain the positive electrode active material, wherein the positive electrode active material includes Na. x Mn y L a M b N c O 2-z-δ F z , 0≤z≤0.1, -0.1≤δ≤0.1. The calcination temperature can be 600℃-1200℃, for example, 600℃, 650℃, 700℃, 750℃, 800℃, 850℃, 900℃, 950℃, 1000℃, 1050℃, 1100℃, 1150℃ or 1200℃, or any range of the above values; the holding time is 10h-20h, for example, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h or 20h, or any range of the above values.

[0083] In addition, the precursor can be pre-calcined and kept at a certain temperature before calcining, as needed. The pre-calcination temperature can be 600℃-900℃, for example, 600℃, 650℃, 700℃, 750℃, 800℃, 850℃ or 900℃, or any range of the above values; the holding time can be 10h-20h, for example, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h or 20h, or any range of the above values.

[0084] Therefore, the positive electrode active material prepared by the solid-state method has a high specific capacity and excellent cycle stability, thereby improving the capacity retention rate of the battery.

[0085] A third aspect of this application discloses a method for preparing a positive electrode active material, comprising: S10: Mix Mn source, L source, M source and N source with water to obtain a mixed solution. Specifically, a mixed solution is obtained by mixing Mn source, L source, M source and N source with water. The molar content of Mn in the Mn source is y, the molar content of L in the L source is a, the molar content of M in the M source is b, and the molar content of N in the N source is c. L includes at least one of Ni, Li, Zn, Cu, Mg, Fe, B, Al, La, Cr, In and Ga; M includes at least one of Ti, Sn, Sb, Bi and Zr; and N includes at least one of Nb, Ta, Mo and W. y ≥ 0.2, 0.1 ≤ a ≤ 0.6, 0 ≤ b ≤ 0.3, 0 <c≤0.05,y+a+b+c=1,40≤a / c≤400。

[0086] It should be noted that the Mn source, L source, M source and N source in this application are conventional materials in the art, and those skilled in the art can select them according to actual needs. For example, the Mn source may include at least one of Mn chloride, manganese sulfate, manganese nitrate and manganese oxalate; the L source may include at least one of L chloride, L sulfuric acid, L nitric acid and L oxalate; the M source may include at least one of M chloride, M sulfuric acid, M nitric acid and M oxalate; and the N source may include at least one of N chloride, N sulfuric acid, N nitric acid and N oxalate.

[0087] S20: React the mixed solution with a precipitant to obtain a precursor. In some embodiments, the mixed solution obtained in step S10 is reacted with a solution containing a precipitant to obtain a precursor, wherein the solution containing the precipitant includes at least one of a hydroxide precipitant solution, a carbonate precipitant solution, or an oxalate precipitant solution.

[0088] S30: The precursor is mixed with a Na source and then calcined. In some embodiments of this application, the molar content of Na in the sodium source is x, where 0.5 ≤ x ≤ 1.2. The obtained precursor and Na source are mixed uniformly by ball milling or mechanical stirring according to the above-mentioned positive electrode active material composition. The mixture is then calcined in a muffle furnace, cooled to room temperature, and mechanically pulverized to obtain the positive electrode active material. The calcination temperature can be 600℃-1200℃, for example, 600℃, 650℃, 700℃, 750℃, 800℃, etc. The temperatures can be 850℃, 900℃, 950℃, 1000℃, 1050℃, 1100℃, 1150℃, or 1200℃, or any range of the above values; the calcination atmosphere can be air or oxygen; and the holding time can be 10h-20h, for example, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, or 20h, or any range of the above values.

[0089] It should be noted that, since Na is lost during calcination, the molar content of Na can be appropriately increased when feeding to compensate for the loss of Na during calcination.

[0090] It should be noted that, as needed, before mixing and calcining the precursor and Na source, the precursor and Na source can be pre-calcined and held at a specific temperature. The pre-calcination temperature can be 600℃-900℃, for example, 600℃, 650℃, 700℃, 750℃, 800℃, 850℃, or 900℃, or any range of the above values. The holding time can be 10h-20h, for example, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, or 20h, or any range of the above values. The Na source can include at least one of Na₂CO₃, NaHCO₃, NaOH, and Na₂O₂.

[0091] It should be noted that if F element needs to be doped in the positive electrode active material, at least one of the Na source, Mn source, L source, M source and N source shall be at least one of its corresponding fluorine-containing salt and other compounds, such as sodium fluoride, manganese fluoride, L fluoride (fluoride salt of L), M fluoride (fluoride salt of M) and N fluoride (fluoride salt of N).

[0092] Therefore, the positive electrode active material prepared by the co-precipitation method has high specific capacity and excellent cycle stability.

[0093] The fourth aspect of this application discloses a positive electrode sheet, comprising the positive electrode active material disclosed in the first aspect of this application and the positive electrode active material prepared by the method disclosed in the second or third aspect of this application.

[0094] The positive electrode typically includes a positive current collector and a positive active material layer disposed on the positive current collector, wherein the positive active material layer includes a positive active material.

[0095] The positive electrode current collector can be a conventional metal foil or a composite current collector (a composite current collector can be formed by setting metal materials on a polymer substrate). As an example, the positive electrode current collector may include at least one of copper foil, aluminum foil, nickel foil, stainless steel foil, stainless steel mesh, and carbon-coated aluminum foil.

[0096] The positive electrode active material includes the positive electrode active material described in the first aspect of this application, the positive electrode active material prepared by the method described in the second aspect, or the positive electrode active material prepared by the method described in the third aspect.

[0097] The positive electrode active material layer may also optionally include a conductive agent and a binder. The conductive agent is used to improve the conductivity of the positive electrode active material layer, and the binder is used to firmly bond the positive electrode active material and the binder to the positive electrode current collector. This application does not specifically limit the types of conductive agents and binders, and they can be selected according to actual needs.

[0098] As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers; the binder may include at least one of styrene-butadiene rubber (SBR), water-based acrylic resin, carboxymethyl cellulose (CMC), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), and polyvinyl alcohol (PVA).

[0099] These materials can all be obtained through commercial means.

[0100] A fifth aspect of this application provides a battery comprising the positive electrode sheet described in the fourth aspect of this application. Therefore, the battery exhibits excellent cycle stability.

[0101] A battery is a device that can be recharged after being discharged, allowing its active materials to be reactivated and continue to be used.

[0102] It is understood that the battery proposed in this application is a sodium-ion battery.

[0103] Typically, a battery consists of a positive electrode, a negative electrode, a separator, and an electrolyte. During charging and discharging, active ions move back and forth between the positive and negative electrodes, inserting and releasing. The separator, positioned between the positive and negative electrodes, serves as a barrier. The electrolyte, acting as a conductor of ions, lies between the positive and negative electrodes.

[0104] [Negative electrode plate] In a battery, the negative electrode typically includes a negative current collector and a negative active material layer disposed on the negative current collector, wherein the negative active material layer includes a negative active material.

[0105] The negative electrode current collector can be a conventional metal foil or a composite current collector (for example, a metal material can be disposed on a polymer substrate to form a composite current collector). As an example, the negative electrode current collector can be a copper foil.

[0106] The specific type of the negative electrode active material is not limited; any active material known in the art that can be used as a negative electrode in sodium-ion batteries can be used. Those skilled in the art can select according to actual needs. As an example, the negative electrode active material may include, but is not limited to, at least one of sodium metal, carbon materials, alloy materials, transition metal oxides and / or sulfides, phosphorus-based materials, and titanate materials. Specifically, the carbon material may include at least one of hard carbon, soft carbon, amorphous carbon, and nanostructured carbon materials; the alloy material may include an alloy material formed from at least one of Si, Ge, Sn, Pb, and Sb; the general formula of the transition metal oxides and sulfides is M. x N y M includes at least one of Fe, Co, Ni, Cu, Mn, Sn, Mo, Sb, and V, and N includes O or S; the phosphorus-based material may include at least one of red phosphorus, white phosphorus, and black phosphorus; the titanate material may include Na2Ti3O7 or Na2Ti6O7. 13 Na4Ti5O 12 Li4Ti5O 12 At least one of NaTi2(PO4)3. These materials are all commercially available.

[0107] The negative electrode active material layer may also optionally include a binder and a conductive agent. The conductive agent is used to improve the conductivity of the negative electrode active material layer, and the binder is used to firmly bond the negative electrode active material and the binder to the negative electrode current collector. This application does not specifically limit the types of conductive agents and binders, which can be selected according to actual needs.

[0108] As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0109] As an example, the adhesive may include at least one of styrene-butadiene rubber (SBR), styrene-butadiene rubber (SBCs), water-based acrylic resin, and carboxymethyl cellulose (CMC).

[0110] The negative electrode active material layer may also optionally include a thickener, such as carboxymethyl cellulose (CMC). However, this application is not limited to this, and other materials that can be used as thickeners for sodium-ion battery negative electrode sheets may also be used.

[0111] Electrolyte The electrolyte may include an electrolyte salt and a solvent.

[0112] As an example, the electrolyte sodium salt may include at least one of sodium hexafluorophosphate, sodium difluorooxalate borate, sodium tetrafluoroborate, sodium dioxalate borate, sodium perchlorate, sodium hexafluoroarsenate, sodium bis(fluorosulfonyl)imide, sodium trifluoromethanesulfonate, and sodium bis(trifluoromethanesulfonyl)imide.

[0113] As an example, the solvent may include at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butyl ester carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE).

[0114] In some embodiments, the electrolyte also includes additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, and additives that improve battery low-temperature performance.

[0115] [Isolation membrane] As for the aforementioned separator, this application does not have any particular limitations. Any known porous structure separator with electrochemical and mechanical stability can be selected according to actual needs. For example, it may include a single-layer or multi-layer film containing at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride.

[0116] This application does not impose any particular limitation on the shape of the battery; it can be cylindrical, square, or any other arbitrary shape. Figure 1 Here is a square-shaped battery 1 as an example.

[0117] In some embodiments, the battery may include an outer packaging. This outer packaging is used to encapsulate the positive electrode, the negative electrode, and the electrolyte.

[0118] In some embodiments, the outer packaging may include a shell and a cover. The shell may include a base plate and side plates attached to the base plate, the base plate and side plates enclosing a receiving cavity. The shell has an opening communicating with the receiving cavity, and the cover can be placed over the opening to close the receiving cavity.

[0119] The positive electrode, negative electrode, and separator can be formed into an electrode assembly using a winding or stacking process. The electrode assembly is encapsulated within the receiving cavity. The number of electrode assemblies contained in the battery can be one or more, and can be adjusted as needed.

[0120] In some implementations, the outer packaging of the battery may include a rigid shell, such as a rigid plastic shell, an aluminum shell, or a steel shell.

[0121] The outer packaging of the battery may also include a pouch, such as a soft pouch. The material of the pouch may be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0122] In some implementations, batteries can be assembled into battery modules, and the number of batteries contained in a battery module can be multiple, with the specific number adjustable according to the application and capacity of the battery module.

[0123] Figure 2 This is battery module 2 as an example. (See reference...) Figure 2 In battery module 2, multiple batteries 1 can be arranged sequentially along the length of battery module 2. Of course, they can also be arranged in any other way. Furthermore, these multiple batteries 1 can be fixed in place using fasteners.

[0124] The battery module 2 may also include a housing with a receiving space in which multiple batteries 1 are housed. In some embodiments, the battery modules may also be assembled into a battery pack, the number of battery modules contained in the battery pack being adjustable according to the application and capacity of the battery pack.

[0125] Figure 3 and 4 This is battery pack 3 as an example. (See reference...) Figure 3 and 4 The battery pack 3 may include a battery box and multiple battery modules 2 disposed within the battery box. The battery box includes an upper body 4 and a lower body 5, with the upper body 4 covering the lower body 5 to form a closed space for accommodating the battery modules 2. The multiple battery modules 2 can be arranged in any manner within the battery box.

[0126] A sixth aspect of this application provides an electrical device that includes the battery proposed in the fifth aspect of this application. Specifically, the battery can serve as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks), electric trains, ships and satellites, and energy storage systems.

[0127] Figure 5 This is an example of an electrical appliance. The electrical appliance includes pure electric vehicles, hybrid electric vehicles, or plug-in hybrid electric vehicles.

[0128] Another example of a power-consuming device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and may use batteries as their power source.

[0129] To make the technical problems, technical solutions, and beneficial effects solved by the embodiments of this application clearer, the following will provide a more detailed description in conjunction with the embodiments and accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of them. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit this application or its applications. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0130] Example 1 Preparation of positive electrode active materials Weigh out a total of 30g of Na₂CO₃, Mn₂O₃, Fe₂O₃, NiO, Al₂O₃, and Nb₂O₅, with the molar ratio of Na, Mn, Fe, Ni, Al, and Nb as shown in Table 1. Pre-grind the obtained sample in an agate mortar and then ball-mill it in a planetary ball mill for 1 hour to obtain a precursor mixture. Place the obtained precursor mixture evenly in an open crucible, and then heat it in a muffle furnace from room temperature to 950℃ at a heating rate of 5℃ / min. Maintain this temperature at 950℃ for 15 hours, and after natural cooling, obtain the positive electrode active material.

[0131] Preparation of the positive electrode sheet The positive electrode active material, conductive agent carbon black (Super P), and binder polyvinylidene fluoride (PVDF) are thoroughly mixed in an appropriate amount of solvent N-methylpyrrolidone (NMP) at a mass ratio of 80:15:5 to form a uniform positive electrode slurry. The positive electrode slurry is then uniformly coated onto the surface of the positive electrode current collector aluminum foil. After drying and cold pressing, it is punched into a disc with a diameter of 14 mm to obtain the positive electrode sheet.

[0132] Preparation of the negative electrode sheet Sodium metal sheets are used.

[0133] Preparation of Electrolyte Equal volumes of ethylene carbonate (EC) and diethyl carbonate (DEC) were mixed to obtain an organic solvent. NaClO4 was then dissolved in the organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0134]

Isolation Film

[0135] [Preparation of button cells] Stack the positive electrode, separator, and negative electrode in sequence, with the separator positioned between the positive and negative electrodes to provide isolation. Add the prepared electrolyte to complete the preparation of the coin cell.

[0136] The composition of the positive electrode active material in the batteries of Examples 1-45 and Comparative Examples 1-10 of this application is shown in Table 1. The positive electrode active materials of Examples 1-45 and Comparative Examples 1-8 were used to prepare batteries. Except for the different composition of the positive electrode active material (see Table 1), the rest were the same as in Example 1.

[0137] Table 1

[0138]

[0139]

[0140] The positive electrode active materials in Examples 1-45 and Comparative Examples 1-10 were subjected to D... v 50. The specific surface area, tap density, compaction density under 300 MPa pressure, pH value of the soaking solution, phase state, and discharge specific capacity and capacity retention of the obtained sodium-ion battery were characterized. The characterization results are shown in Table 2.

[0141] Test method: 1. Testing of phase state, space group, and interlayer spacing of positive electrode active material: Grind the sample to be tested into a fine powder in an agate mortar and pestle in a drying room or glove box, then pass it through a 350-mesh sieve. Take an appropriate amount of the sieved sample and place it in the center of the sample holder groove, ensuring the loose sample powder is slightly higher than the sample holder plane. Gently press a glass slide onto the sample surface to level it with the frame plane, and scrape off any excess powder. After sample preparation, use a Brucker D8A_A25 X-ray powder diffractometer (Brucker AxS, Germany) with CuK... α The X-ray source was X-rays with a wavelength λ = 1.5406 Å. The scanning 2θ angle range was 5°–60°, and the scanning rate was 4° / min. The phase state of the positive electrode active material was determined based on the position of characteristic peaks in the XRD pattern. Characteristic peaks within the 40.5°–42.5° scanning 2θ angle range indicated that the positive electrode active material was in the O3 phase, with space groups including… The characteristic peaks in the range of 48° to 50° when scanning the 2θ angle indicate that the positive electrode active material is the P2 phase, and the space group includes P63 / mmc.

[0142] 2. D of the positive electrode active material v 50 measurements The particle size distribution was determined using a laser particle size analyzer (Malvern Master Size 2000). The specific testing procedure was as follows: Take an appropriate amount of the sample to be tested (the sample concentration should be 8%-12% light-blocking level), add 20 ml of deionized water, and sonicate for 5 min (53 kHz / 120 W) to ensure complete dispersion of the sample. Then, the sample was measured according to the standard GB / T19077-2016 / ISO 13320:2009.

[0143] 3. Tap density measurement The weighed positive electrode active material is loaded into the graduated cylinder of the tapping device, and the graduated cylinder is fixed on the support. Rotating the cam causes the guide rod to slide the support up and down, striking the anvil. The device vibrates at 250±15 times per minute for 12 minutes. The volume of the positive electrode active material in the graduated cylinder is measured; the ratio of the mass of the positive electrode active material to its volume is the tap density of the positive electrode active material.

[0144] The formula for calculating tap density is: ρbt = m0 / V Where ρbt is the tap density, in g / cm³. 3 m0 — Mass of the positive electrode active material, in grams V – Volume of the positive electrode active material after tapping (volume of the measuring cup), cm 3 .

[0145] 4. Compacted density of the positive electrode active material under 300MPa pressure The method for determining the compaction density of positive electrode active materials under 300 MPa pressure is based on GB / T5162-2006.

[0146] 5. pH value determination of the immersion solution for positive electrode active materials Take 2g of positive electrode active material and place it in a beaker. Add 18mL of deionized water and stir vigorously for 1min. After standing for 30min, use a pH meter to test the pH of the supernatant.

[0147] 6. Battery capacity retention test: At 25℃, after fabricating a coin cell using layered oxide cathode active material, it was charged to 4.3V at a constant current density of 10mA / g, and then discharged to 1.5V at a constant current density of 10mA / g, yielding the discharge specific capacity C0 of the coin cell. Subsequently, it underwent 50 charge-discharge cycles at a constant current density of 10mA / g, and the discharge specific capacity of the 50th cycle was taken as C1. The capacity retention rate of the layered oxide cathode active material after 50 cycles = C1 / C0.

[0148] 7. Discharge specific capacity test: At 25℃, after the layered oxide positive electrode active material is prepared into a coin cell, it is charged to 4.3V with a constant current density of 10mA / g, and then discharged to 1.5V with a constant current density of 10mA / g to obtain the discharge specific capacity C0 of the coin cell.

[0149] 8. SEM testing The tests were performed using a field emission scanning electron microscope (Zeiss Gemini 360) according to the JY / T010-1996 standard.

[0150] Table 2

[0151] Conclusion: As shown in Table 2, the sodium-ion batteries corresponding to Examples 1-45 can simultaneously optimize their discharge specific capacity and capacity retention after 50 cycles. The sodium-ion batteries in Comparative Examples 1-10, however, cannot simultaneously improve their discharge specific capacity and capacity retention after 50 cycles. Figure 6 It can be seen that the capacity retention rate of Example 18 is significantly higher than that of Comparative Example 4, as indicated by the appendix. Figure 7 and attached Figure 8 As can be seen, the surface of the positive electrode active material of this application has no cracks after 50 cycles, indicating that the battery of this application can have both excellent specific capacity and cycle stability.

[0152] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and not to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. These modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application, and they should all be covered within the scope of the claims and specification of this application. In particular, as long as there is no structural conflict, the various technical features mentioned in the embodiments can be combined in any way. This application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

[0153] In this invention, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this invention, "a plurality of" means two or more, unless otherwise explicitly specified.

[0154] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0155] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.

Claims

1. A battery, characterized in that, The positive electrode includes a positive electrode sheet, wherein the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes Na. x Mn y L a M b N c O 2-z-δ F z Wherein, L includes at least one of Ni, Li, Zn, Cu, Mg, Fe, B, Al, La, Cr, In, and Ga; M includes at least one of Ti, Sn, Sb, Bi, and Zr; N includes at least one of Nb, Ta, Mo, and W; 0.5 ≤ x ≤ 1.2, y ≥ 0.2, 0.1 ≤ a ≤ 0.6, 0 ≤ b ≤ 0.3, 0 <c≤0.05,y+a+b+c=1,0≤z≤0.1,-0.1≤δ≤0.1,40≤a / c≤400。 2. The battery according to claim 1, characterized in that, 50≤a / c≤200.

3. The battery according to claim 1, characterized in that, N includes at least one of Nb and Ta.

4. The battery according to claim 1, characterized in that, L includes at least one of Ni, Zn, Cu, Mg, Fe, B, and Al.

5. The battery according to claim 1, characterized in that, M includes at least one of Ti, Bi, and Zr.

6. The battery according to claim 1, characterized in that, At least one of the following conditions must be met: (1)0.7≤x≤1; (2)0.3≤y≤0.5; (3)0.4≤a≤0.6; (4)0.01≤b≤0.1; (5)0.005≤c≤0.015; (6)0≤z≤0.005。 7. The battery according to claim 1, characterized in that, 3≤y / (b+c)≤40.

8. The battery according to claim 7, characterized in that, 6≤y / (b+c)≤30.

9. The battery according to any one of claims 1-8, characterized in that, The positive electrode active material includes an O3 phase, and the space group of the O3 phase positive electrode active material includes... The interlayer spacing of the positive electrode active material in the O3 phase is 0.53nm-0.55nm.

10. The battery according to claim 9, characterized in that, The positive electrode active material includes a P2 phase, the space group of the P2 phase positive electrode active material includes P63 / mmc, and the interlayer spacing of the P2 phase positive electrode active material is 0.54nm-0.57nm.

11. The battery according to claim 10, characterized in that, At 25°C, the pH value of the immersion solution for the positive electrode active material is 7-13.

12. The battery according to claim 11, characterized in that, The pH value of the soaking solution for the positive electrode active material is 11-12.

5.

13. The battery according to claim 11, characterized in that, At least one of the following conditions must be met: (1) The particle size D of the positive electrode active material v 50 is 3μm-30μm; (2) The specific surface area of ​​the positive electrode active material is 0.1 m². 2 / g-5m 2 / g; (3) The tap density of the positive electrode active material is 1 g / cm³. 3 -3g / cm 3 ; (4) The compaction density of the positive electrode active material under a pressure of 300 MPa is 3.0 g / cm³. 3 -4.0g / cm 3 .

14. The battery according to claim 13, characterized in that, At least one of the following conditions must be met: (1) The particle size D of the positive electrode active material v 50 is 5μm-15μm; (2) The specific surface area of ​​the positive electrode active material is 0.3 m². 2 / g-3m 2 / g; (3) The tap density of the positive electrode active material is 1.5 g / cm³. 3 -2.5g / cm 3 .

15. An electrical appliance, characterized in that, The battery includes any one of claims 1-14.